Pengaruh Label Halal Dan Harga Terhadap Keputusan Pembelian Skin Care Ms Glow Di Maya Store Agen Muara Bungo - Hamirul, Hamirul; Rusnaini, Sasmita; Pratiwi, Widya; Ariyanto. M, Ariyanto. M; Albadry, Syah Amin; Darmawanto, Darmawanto (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
This study aims to determine the effect of halal labels and prices on purchasing decisions for MS Glow skincare either partially or simultaneously. by using the Associative method with a quantitative approach. The results obtained are the effect of the halal label on the purchase decision to buy MS Glow Skincare at the MS Glow Maya Store Agent Muara Bungo based on the partial test results obtained that the halal label variable has an effect on purchasing decisions. If the halal label is getting better, the decision to buy MS Glow Skincare will also increase at the MS Glow Maya Store Agent Muara Bungo. The effect of price on purchasing decisions to buy MS Glow Skincare at MS Glow Maya Store Agent Muara Bungo based on the results of the partial test obtained that the price variable has an effect on purchasing decisions. If the price is getting better, the decision to buy MS Glow Skincare Reseller will also increase at the Maya Store Agent Muara Bungo The magnitude of the effect of halal labels and prices on purchasing decisions of MS Glow Skincare Resellers at the Maya Store Agen Muara Bungo based on the results of the coefficient of determination test obtained by 86.3%, while the remaining 13.7% is influenced by other dimensions outside the study.